2018
DOI: 10.1002/ijc.31867
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin analogs: Their roles in pancreatic cancer growth and metastasis

Abstract: Curcumin is a polyphenolic constituent of turmeric that is known to have various molecular effects in preclinical models, leading to prevention and anti-cancer properties. In clinical trials, curcumin has failed to demonstrate activity against pancreatic cancer possibly due to its low bioavailability and potency. Using the curcumin molecular model, our group and others have synthesized several analogs with better bioavailability and higher potency in pancreatic cancer in vitro and xenograft models. This mini r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 64 publications
(182 reference statements)
0
28
0
Order By: Relevance
“…Therefore, it is uncertain whether the discovered mechanisms of curcumin analog apply to curcumin itself. Moreover, the biosafety of these analogs has not been verified by long-term practice, so they are still a long way to the clinical translation [ 51 , 52 ]. Altogether, to address the problems of low bioavailability and potency of curcumin itself may be a more direct and efficient mean of curcumin being further translated as favorable pharmacotherapy against pancreatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is uncertain whether the discovered mechanisms of curcumin analog apply to curcumin itself. Moreover, the biosafety of these analogs has not been verified by long-term practice, so they are still a long way to the clinical translation [ 51 , 52 ]. Altogether, to address the problems of low bioavailability and potency of curcumin itself may be a more direct and efficient mean of curcumin being further translated as favorable pharmacotherapy against pancreatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Previously the effect of nitrogen introduced in a form of 4‐piperidone structure to curcumin analogues was studied , . Many of the analogues demonstrated very good antiproliferative activities . Moreover, it was demonstrated that addition of thiols (a known mechanism of protein binding) to α,β‐unsaturated‐β′‐amino ketones (enones with additional β amino nitrogen) was significantly faster than addition to unmodified enones .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, one main drawback to limit its use in medical application is rapid metabolism and low bioavailability 114 . As a consequence, many approaches have been adopted to circumvent this problem, including engineering its analogs by modulating curcumin structure 115 and improving its delivery systems through loading in nanoparticles 116 . Take HO-3867 for example.…”
Section: Resveratrolmentioning
confidence: 99%